Physicochemical, functional, pasting, thermal, and sensory properties of purple yam (dioscorea alata L.) powder - Rallos, Frances Jaye N.; Luna, Myrna Benita Z. (Quezon City College of Home Economics, University of the Philippines Diliman, 2023)
Purple yam powder is an ingredient that enhances the physico-chemical and sensory properties of various Philippine food products. The purple yam powder produced by a food industry collaborator in Cavite, Philippines, had an unstable pale color. To improve its color, the standard process used by the company was modified by introducing ascorbic acid pre-treatment, uniform tuber slicing, steaming, and drying process standardization in another study. As a sequel study, this research compared the physicochemical, functional, pasting, thermal, and sensory properties of the yam powder from the modified process with the powder produced using the standard process. Results showed that the modified process significantly (p < 0.05) increased moisture content and decreased ash and total carbohydrate contents. In terms of color, a significant (p < 0.05) reduction in hue angle (19.931 ± 9.713) and lightness (47.217 ± 1.105) and a significant (p < 0.05) increase in chroma (8.3245 ± 0.490) were observed. This indicates that a redder, darker, and more vivid powder was produced using the modified process. Furthermore, a ΔE* of 4.390 ± 1.655 demonstrates that the human eye perceives the color difference between the yam powders. The powder produced through the modified process exhibited a decrease in water binding capacity, as well as a rising trend of swelling power and solubility was observed as the temperature increased. A lower water binding capacity of the purple yam from the modified process may be attributed to the hydroxyl groups forming hydrogen and covalent bonds between their starch chains instead of water. The swelling power and solubility of the purple yam powder over the range of temperatures indicate its heterogeneity. Additionally, significant changes in pasting and gelatinization properties were noted. Higher pasting viscosities and higher (p <0.05) retrogradation of the modified process purple yam powder showed potential as a high thickening power ingredient. On the other hand, higher peak temperatures and enthalpy of the standard process purple yam powder suggested structural stability, making it more resistant to gelatinization. Upon application of the standard and modified purple yam powders in ube halaya, significantly (p < 0.05) higher consumer acceptability scores for color, ube aroma and flavor, and mouthfeel. Also, it had a significantly (p < 0.05) higher overall acceptability of “like moderately.” Information obtained from this study will benefit all stakeholders involved in the use of yam powders as an ingredient in food formulations. It is recommended that shelf stability and food applications of the yam powder produced from the modified process be established.
Thesis (Bachelor of Science in Food Technology) -- University of the Philippines Diliman
Bibliography: pages 60-69.
Keywords: Yams -- Thermal properties; Yams -- Philippines -- Cavite